1989
DOI: 10.1007/bf00285287
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria reflects widespread vascular damage

Abstract: Albuminuria in Type 1 (insulin-dependent) diabetes is not only an indication of renal disease, but a new, independent risk-marker of proliferative retinopathy and macroangiopathy. The coincidence of generalised vascular dysfunction and albuminuria, advanced mesangial expansion, proliferative retinopathy, and severe macroangiopathy suggests a common cause of albuminuria and the severe renal and extrarenal complications associated with it. Enzymes involved in the metabolism of anionic components of the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
687
4
22

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,286 publications
(751 citation statements)
references
References 99 publications
30
687
4
22
Order By: Relevance
“…Higher albumin excretion reflects dysfunction in small arteries, probably in part due to endothelial dysfunction. [21][22][23] This concept is consistent with our observed association between albumin excretion rate and SAE, but not LAE. Similarly, cell adhesion molecules play an important role in the pathogenesis of atherosclerosis by mediating the binding of leukocytes to the endothelium.…”
Section: Discussionsupporting
confidence: 91%
“…Higher albumin excretion reflects dysfunction in small arteries, probably in part due to endothelial dysfunction. [21][22][23] This concept is consistent with our observed association between albumin excretion rate and SAE, but not LAE. Similarly, cell adhesion molecules play an important role in the pathogenesis of atherosclerosis by mediating the binding of leukocytes to the endothelium.…”
Section: Discussionsupporting
confidence: 91%
“…Albuminuria is well recognized as a good biomarker for endothelial dysfunction and atherosclerotic vascular disease, including stroke 28, 29. As we therefore expected, the present study showed that higher UACR level was significantly associated with a higher risk for the development of VaD, especially VaD with prior stroke events.…”
Section: Discussionsupporting
confidence: 79%
“…Anaemia is also independently associated with albuminuria ( Fig. 2), an early marker of microvascular inflammation and damage [14], which, like anaemia [3], precedes declining renal function associated with late-stage nephropathy. Recently, it has also been shown that, even in the absence of albuminuria, anaemia in patients with diabetes is largely the result of impaired renal functioning [15].…”
Section: Which Patients Will Have Anaemia?mentioning
confidence: 99%